Public licenses as causes for justification under economic criminal law - Silva Carrillo, Kevin André (2025)
In this paper the author analyzes the current theoretical discussion of public licenses in the theory of crime, and particularly its treatment in the field of economic criminal law. With a dogmatic-legal and critical analysis, the initial pieces of a model of systematic-rational foundation of administrative authorizations as a cause of justification are proposed.